Comprehensive dermatologic drug theraphy - Wolverton, Stephen E. (Saunders/Elsevier, 2013)
Safely and effectively treat a full range of skin disorders with Comprehensive Dermatologic Drug Therapy, 3rd Edition! This trusted dermatology reference provides concise, complete, up-to-date guidance on today's full spectrum of topical, intralesional, and systemic drugs. Dr. Steven E. Wolverton and a team of leading international experts clearly explain what drugs to use, when to use them, and what to watch out for.